Establishing the Green Human Resource Management Practices Model of SMEs in Malaysia - Mohd Yusoff, Yusmani; Abdullah, Haim Hilman; Halid, Hafinas (KOGAION PUBLISHING CENTER, 2020)
Research has shown a relationship between proactive adoption of environmental performance practices and organization performance; however, there was lack of research, particularly on the small and medium enterprises (SMEs) in examining the impact of human resources management (HRM) practices. A study revealed that 60 percent of all carbon dioxide emissions and 70 percent of all pollutions are caused by SMEs. Hence, SMEs need to establish effective human resource management in managing their environmental actions, especially if the SMEs intended to meet the sustainability criteria. This paper examined the component of green HRM practices model implementation in Malaysian SMEs industry. It provides a better understanding of the current green human resource management practices implemented by SMEs in Malaysia.